The Role of Local Product Quality, Destination Uniqueness, and Access to Information in Increasing Agro-Tourism Consumer Satisfaction in Bogor - Susiang, Maria Imelda Novita; Latif, Latif; Setiyawan, Heri (Westscience Press, 2025)
This study investigates the role of local product quality, destination uniqueness, and access to information in enhancing agro-tourism consumer satisfaction in Bogor. A quantitative research design was employed, involving 150 respondents who had visited agro-tourism destinations. Data were collected using a structured questionnaire and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that local product quality, destination uniqueness, and access to information significantly and positively influence consumer satisfaction, collectively explaining 62% of its variance. These results highlight the critical role of quality products, unique destination attributes, and effective information dissemination in shaping consumer experiences. Practical recommendations for agro-tourism stakeholders include prioritizing product quality, emphasizing destination distinctiveness, and improving communication strategies.